Free Officers’ Revolution and the Criticism of the Totalitarian Regime in the Egyptian Novel Under the Light of the Works of Naguip Mahfouz, Abd al-Rahman Sharqawi, and Alaa Al Aswany - Asiye Çelenlioğlu (Şarkiyat Mecmuası)
In Egyptian literature, the art of novel that records the dairy of life has been formed by social life, and since its early examples, which are accepted as the first steps of modern prose, it has undertaken such a duty to shape social and political structure. Pieces with a national independence theme substitute for the early novels, which were trying to find answers to the problems occurred by westernization, after Egypt retrieve its native rulers with the 1952 revolution, democratic life became the main theme of the novels. The revolution that waswelcomed by society due to reforms such as land reform and free education evolved theocracy after some time, and its legacy kept influencing Egypt’s present political life. At a time when denouncements and arrestments spread fear, novel writers generally avoided politics and were occupied with improvements in individuals or society. In that period, while Naguip Mahfouz was criticizing the regime with his symbolic novels Abd al-Rahman Sharqawi, who was crossing the line of politics, was trying to find excuses for the existing problems with his novel “Fellah” which was greeting reforms with great excitement. Alaa Al Aswany, who contemporarily problematized Egypt’s political history, was also among the few writers who out loudly expressed their opinions about the revolution. This study will examine the period mentioned by these three writers and point out how the issue of autocracy, which became a legacy in Egyptian politics, found place in their novels.